2015
DOI: 10.1093/nop/npv024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and molecular characterization of pediatric glioblastoma treated with postoperative radiotherapy with concurrent and adjuvant temozolomide: a single institutional study of 66 children

Abstract: Background Glioblastoma (GBM) in children is rare. Pediatric GBM have a distinct molecular profile as compared to adult GBM. There are relatively few studies of pediatric GBMs and no standard of care on adjuvant therapy. We aimed to evaluate the clinical outcome and molecular profile of pediatric GBM. Methods and Materials Between 2004 and 2013, 66 consecutive children with histologically proven GBM were identified from our d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
4
9
0
Order By: Relevance
“…In this study, the following genetic markers were evaluated: the IDH1 mutation was tested in 29 patients and was detected in 6. The IDH1 mutation is considered a strong predictor of a better outcome in adult GBMs and is found in most patients with secondary adult GBMs 11 . However, the IDH1 mutation is rare in pediatric high-grade gliomas 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the following genetic markers were evaluated: the IDH1 mutation was tested in 29 patients and was detected in 6. The IDH1 mutation is considered a strong predictor of a better outcome in adult GBMs and is found in most patients with secondary adult GBMs 11 . However, the IDH1 mutation is rare in pediatric high-grade gliomas 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Maximal safe resection is the first step of HHG treatment. Many retrospective series reported extent of resection (EOR) as the only one or one of the main prognostic factors influencing OS ( Table 4 ) [ 1 , 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 19 , 22 , 25 , 27 , 29 , 30 ]. Additionally, SEER analysis performed by Adams H. showed that gross total resection is independently associated with improved OS in GBM patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…RT as adjuvant treatment (combined with CTH in some patients) was used in almost all of the studies. Doses prescribed were usually within the range of 54 to 60 Gy, given in 1.8 to 2 Gy fractions, and covered tumor (GTV), along with tumor bed and additional margins of 2 to 2.5 cm (CTV,PTV) [ 7 , 8 , 9 , 10 , 11 , 12 , 14 , 17 , 19 , 22 , 24 , 25 , 28 ]. Some authors limited the dose to 54 Gy in cases of children 6 years of age or younger, as well as included patients irradiated to only 45 Gy [ 6 , 17 , 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent series of pediatric GBM has reported encouraging results and manageable toxicity when treated with concurrent radiation and TMZ followed by maintenance TMZ. [36] Another series of 66 patients reported recently, [37] found the median survival to be 15 months when treated with the same schedule. In addition, MGMT methylation and p53 over expression was not shown to impact OS.…”
Section: Treatment For Pediatric Glioblastoma Multiformementioning
confidence: 99%